New data on the genus Rhytidicolus (Aranei: Rhytidicolidae), with redescription of R. structor Simon, 1889 and description of a new species - Ríos Tamayo, Duniesky (2024)
The type species of the previously monotypic genus Rhytidicolus Simon, 1889, R. structorSimon, 1889 (Venezuela), is redescribed from the female type series. Additionally, a new species of the genus, R. hoferi sp.n., based on males, is described from Manaus, Amazonas in Brazil. The two species can be well distinguished one from another in their dissimilar structure of the cheliceral rastellum (biserial vs. uniserial in the former and latter species, respectively). The previously unknownmale belonging to the genus is described for the first time.